The color-adjustable phosphor Sr4La(PO4)3O:Ce3+,Tb3+,Mn2+ of WLEDs: luminescence and transfer of energy characteristics - Phuc Dang Huu; Phan Xuan Le (Bulletin of Electrical Engineering and Informatics, 2022)
A high heat solid-state technique was used to produce a set of phosphor Sr4La(PO4)3O:Ce3+,Tb3+,Mn2+ (Sr:Mn). In Sr4La(PO4)3O, the luminescence characteristics, heat resistance, and energy conversion between Ce3+ and Tb3+ as well as Mn2+ were thoroughly researched. Introducing the activator Ce3+ particles can significantly increase the dim green-emitting from Tb3+ and the red-emitting from Mn via energy conversion. The color of the emissions might be changed by adjusting the Ce3+/Tb3+ and Ce3+/Mn2+ ion ratios. In the Sr4La(PO4)3O: 0.12 Ce3+,0.3 Mnz2+ specimen, we achieved white-emitting illumination, yielding hue coefficients (0.3326, 0.3298), showing that the phosphor Sr:Mn could have promising implications for white light-emitting diodes (WLEDs).